Automatic stock picking based on insider trades - Arushi, Datta. (2013)
This study analyzes legal insider trades in Singapore to determine whether insiders can make profits through these trades. Insider purchases are studied through event study analysis and a consequent regression analysis over a short-term period of 60 days and a longer-term period of 120 days. Abnormal returns are found to exist in both short-term and long-term, but there is a higher probability and potential to make abnormal profits in the longer term. By using regression analysis, maximum values of abnormal returns are found to be related linearly to volume of shares traded. It is also found that trades of medium-sized companies and made by substantial shareholders have the highest potential to make abnormal returns. The challenge for outsiders, who are trying to replicate such insider trades to make profits, is timing their buys as close as to the insider’s buy and selling when maximum returns are made.